Facile design of autogenous stimuli-responsive chitosan/hyaluronic acid nanoparticles for efficient small molecules to protein delivery. Issue 32 (8th July 2020) - Sabourian, Parinaz; Ji, Jeff; Lotocki, Victor; Moquin, Alexandre; Hanna, Ramez; Frounchi, Masoud; Maysinger, Dusica; Kakkar, Ashok
Abstract : Chitosan is functionalized with oxidative stress-sensitive thioketal entities in a one-pot methodology, and self-assembled into drugs or protein loaded dual stimuli responsive nanoparticles, which kill glioblastoma cells and increase nerve outgrowth. Abstract : Easily assembled and biocompatible chitosan/hyaluronic acid nanoparticles with multiple stimuli-responsive ability are ideally suited for efficient delivery of therapeutic agents under specific endogenous triggers. We report a simple and versatile strategy to formulate oxidative stress and pH-responsive chitosan/hyaluronic acid nanocarriers with high encapsulation efficiencies of small drug molecules and nerve growth factor protein. This is achieved through invoking the dual role of a thioketal-based weak organic acid to disperse and functionalize low molecular weight chitosan in one-pot. Thioketal embedded chitosan/hyaluronic acid nanostructures respond to oxidative stress and show controlled release of quercetin, curcumin and NGF. Lowering the pH in the buffer solution led to higher quercetin release from NPs than at physiological pH, and mimicked the nanoparticle behavior in the environment of early to late endosomes. Curcumin and quercetin loaded NPs killed glioblastoma cells with high efficiency, and NGF-loaded nanoparticles retained biological activity of the protein and increased peripheral nerve outgrowth in explanted mouse dorsal root ganglia.